2010
DOI: 10.1111/j.1469-8137.2010.03233.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in resistance to acetyl‐coenzyme A carboxylase‐inhibiting herbicides across the range of the arable weed Alopecurus myosuroides (black‐grass)

Abstract: Summary• The geographical structure of resistance to herbicides inhibiting acetyl-coenzyme A carboxylase (ACCase) was investigated in the weed Alopecurus myosuroides (black-grass) across its geographical range to gain insight into the process of plant adaptation in response to anthropogenic selective pressures occurring in agricultural ecosystems.• We analysed 297 populations distributed across six countries in A. myosuroides' main area of occupancy. The frequencies of plants resistant to two broadly used ACCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 46 publications
6
119
1
3
Order By: Relevance
“…The evolution of resistant populations in close geographic proximity possibly have evolved independently, as it has been observed in regions of Australia (Owen et al 2011). Several studies have demonstrated the multiple genetic origins of herbicide resistance in crop areas; Délye et al (2004Délye et al ( , 2010 found that resistance to ACCase-inhibiting herbicides in populations of Alopecurus myosuroides in Europe (Germany, Belgium, France, Netherlands, United Kingdom and Turkey) had a different evolutionary origin because of different weed management programs in each country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of resistant populations in close geographic proximity possibly have evolved independently, as it has been observed in regions of Australia (Owen et al 2011). Several studies have demonstrated the multiple genetic origins of herbicide resistance in crop areas; Délye et al (2004Délye et al ( , 2010 found that resistance to ACCase-inhibiting herbicides in populations of Alopecurus myosuroides in Europe (Germany, Belgium, France, Netherlands, United Kingdom and Turkey) had a different evolutionary origin because of different weed management programs in each country.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in localities in close spatial proximity, such as in the case of Alopecurus myosuroides Huds. in Europe (Délye et al 2004, Délye et al 2010. Further, the cultural practices that include the sharing of equipment and seeds, along with seed and pollen dispersal, enable resistant biotypes to disperse over large areas (Afentouli & Eleftherohorinos 1996).…”
Section: Author Contributionsmentioning
confidence: 99%
“…The TaqMan technology can combine two probes with two different fluorochromes, making it possible to detect two different alleles. TaqMan assays have been developed to genotype ALS (e.g., Warwick et al 2008) or ACCase (e.g., Délye et al 2010).…”
Section: Detecting Mutationsmentioning
confidence: 99%
“…Brutus DNA extraction basically consists of grinding a plant fragment in a salty buffer, then boiling it to release DNA from plant tissues (Délye et al 2002). The quality and quantity of the DNA solution is sufficient to provide DNA templates suitable for a range of PCR-based techniques, ranging from basic PCRs to sophisticated techniques such as TaqMan (e.g., Délye et al 2010). This easy DNA extraction protocol is fast and costs almost nothing.…”
Section: Dna and Rna Basicsmentioning
confidence: 99%
“…Herbicide-resistance evolution in the susceptible populations may be triggered due to high level of genetic diversity that supports the increase in the adaptation capacity of more durable species. Geographical location differences provide information on the pathway and mechanisms of resistance propagation (Menchari et al, 2007;Delye et al, 2010;Duhoux et al, 2017;Karn and Jasieniuk, 2017).…”
Section: Introductionmentioning
confidence: 99%